2017
DOI: 10.5194/nhess-17-1305-2017
|View full text |Cite
|
Sign up to set email alerts
|

Storm-wave trends in Mexican waters of the Gulf of Mexico and Caribbean Sea

Abstract: Abstract. Thirty-year time series of hindcast wave data were analysed for 10 coastal locations along the eastern Mexican coast to obtain information about storm events occurring in the region, with the goal of examining the possible presence of interannual trends in the number of storm-wave events and their main features (wave height, duration and energy content). The storms were defined according to their significant wave height and duration, and the events were classified as related to either tropical cyclon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Thus, sea breezes play an important role in nearshore hydrodynamics [22] and sediment transport [23]. Furthermore, Central American cold surge (CACS) events, associated with cold-front passages, generate NNW swell waves that occur during winter months [24]. Appendini et al [25] found that the net potential (westward) of sediment transport in the area is approximately 35,000 m 3 /year and that such value is highly sensitive to shoreline orientation.…”
Section: Descriptionmentioning
confidence: 99%
“…Thus, sea breezes play an important role in nearshore hydrodynamics [22] and sediment transport [23]. Furthermore, Central American cold surge (CACS) events, associated with cold-front passages, generate NNW swell waves that occur during winter months [24]. Appendini et al [25] found that the net potential (westward) of sediment transport in the area is approximately 35,000 m 3 /year and that such value is highly sensitive to shoreline orientation.…”
Section: Descriptionmentioning
confidence: 99%
“…In 1979, the Ixtoc 1 platform within the Cantarell Oil Complex experienced a subsurface blowout that leaked for more than 9 months; ultimately releasing ~3 million barrels of oil into the Bay of Campeche and southern GoM 10 . The narrow shelf and large wave action in the southwestern GoM may result in the continuous flushing and removal of oil contamination and thus the reduction of chronic exposures in this region 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, some researchers have studied the impacts of wind waves and storm surges associated with hurricanes and cold fronts on the Mexican coast. Based on a 30-yr wave hindcast, Appendini et al (2014) found that in the Gulf of Mexico (GoM) the wave climate is mainly modulated by autumn-winter cold fronts, whereas extreme wave climate is modulated by both hurricanes and Nortes, which are anticyclonic cold surges that enter the GoM from North America, generating strong northerly winds and, therefore, presenting ideal conditions for fetch that cause mature wind waves (Ojeda et al, 2017). During Nortes in the GoM, the sustained prevailing winds blow southward and southeastward depending on the origin and orientation of fronts (Henry, 1979); therefore, they are expected to generate a displacement of sea waters to the south, where the wide continental shelf in the southern GoM favors the amplification of the storm surge processes.…”
Section: Introductionmentioning
confidence: 99%